An Alternative Approach to Building Construction: Natural Building Techniques - Erbil, Yasemin (European Journal of Sustainable Development, 2018)
Concerns about the environment around the world are increasing in recent years. As a countermeasure to these concerns, interest in natural building techniques has begun to increase because of the high environmental, social and economic costs of existing construction methods and the potential for natural structures to be a solution to the problem of sustainable living. With natural building techniques it is possible to construct buildings with materials and techniques that are ecologically sound, culturally sensitive, based on local resources and skills, and affordable to local residents. Adobe buildings, cob buildings, earthbags, rammed earth buildings, straw bale buildings, earthships are among the construction techniques utilized for this purpose. In this article, natural building techniques are introduced in a general framework. Increasing usage of natural construction techniques that have the potential to be a solution to the environmental problems in the world by the construction professionals and the construction sector, and supporting developments with research, supporting volunteers, who will take steps in this field, with government policies, and increasing the interest of the users and their awareness should be regarded as a necessity. Keywords: natural buildings, earth buildings, straw bale buildings, earthships